Pharmacokinetic Interaction of Zonisamide in Rats. Effect of Zonisamide on Other Antiepileptics - KIMURA, Masahiko; MIYAKE, Katsushi; TANAKA, Naomi; KITAURA, Teruaki; KIMURA, Yasuhiro; FUKUCHI, Hiroshi (Biological & pharmaceutical bulletin, 1993)
The effects of zonisamide (ZNS) on the pharmacokinetics of phenobarbital (PB), valproic acid (VPA), carbamazepine (CBZ) and phenytoin (PHT) were investigated in rats. Additionally, the influence of ZNS on the serum protein binding, erythrocyte distribution and metabolism of these antiepileptics was studied in vitro. The t1/2 and AUC values of PB were significantly increased by ZNS coadministration, and a significant decrease in the Vd/F value of PHT was observed after multiple dosing of ZNS. By contrast, ZNS showed no significant effect on VPA and CBZ kinetics. No significant effect of ZNS was observed in the serum protein binding, erythrocyte distribution or metabolism of other antiepileptics. These results suggest that ZNS has little effect on the pharmacokinetic behaviors of other antiepileptic drugs.